A vezetés funkcióinak és feladatainak értelmezése az új menedzsment irányzatokban - Láczay, Magdolna (Közép-Európai Közlemények, 2015)
Due to the achievements of Taylor the science of management gained place in modern scientific life in the past century and was soon supplemented by several new theories. Nowadays the classical theories are supposed to be modernized. The most important explanation behind seems to be the act that almost all trends are over a hundred years old and have regulated the science of management by the flourishing capitalist organizations up to these days (focusing on growing profit and efficiency) while social environment lacked sufficient attention. The problem has risen on both global and local levels. Processes different from those of the global organizations can be seen in the small settlements of the North-Plain region, where the elected leader mayors carry out not only local dministrative but also management and public authority duties. They also supervise settlement management while many of them have an enterprise on their own. The unique duties of the various functions reflect that it is impossible to adapt to them with one single method while the increase of personal power raises further problems.